Fast magnetic twister and plasma perturbations in a three-dimensional coronal arcade - Murawski K.; Srivastava A.K.; Musielak Z.E. (My University, 2025)
We present results of three-dimensional (3D) numerical simulations of a fast magnetic twister excited above a foot-point of the potential solar coronal arcade that is embedded in the solar atmosphere with the initial VAL-IIIC temperature profile, which is smoothly extended into the solar corona. With the use of the FLASH code, we solve 3D ideal magnetohydrodynamic equations by specifying a twist in the azimuthal component of magnetic field in the solar chromosphere. The imposed perturbation generates torsional Alfvén waves as well as plasma swirls that reach the other foot-point of the arcade and partially reflect back from the transition region. The two vortex channels are evident in the generated twisted flux-tube with a fragmentation near its apex which results from the initial twist as well as from the morphology of the tube. The numerical results are compared to observational data of plasma motions in a solar prominence. The comparison shows that the numerical results and the data qualitatively agree even though the observed plasma motions occur over comparatively large spatio-temporal scales in the prominence. © 2014. The American Astronomical Society. All rights reserved..